Good tourism governance and tourism development in Bira village - Velayati, Muhammad Fadillah; Ahmad, Badu (Edelweiss Applied Science and Technology, 2024)
This research aims to ensure sustainable tourism development in Bira Village, emphasizing environmental and cultural preservation. Effective tourism management must ensure the sustainable use of natural resources, including water, energy, and waste management, to prevent environmental degradation. Additionally, planned and sustainable tourism development can empower local communities through training and capacity building, ensuring economic benefits are directly felt by the community.The Indonesian government has strengthened the tourism sector with a focus on sustainability, identifying key destinations and supporting cultural and environmental conservation initiatives. The establishment of the Indonesian Tourism Fund supports high-quality and sustainable tourism development by financing infrastructure, destination promotion, human resource training, and environmental conservation projects. Bira Village boasts 12 maritime tourism destinations along the Bulukumba coast, with five managed by the government and seven by local communities. Despite its potential, Bira Village has not been fully optimized for tourism development. This study analyzes the collaboration between the government, private sector, and local communities to achieve sustainable tourism development in Bira Village. Using a qualitative research approach with Interpretative Phenomenological Analysis (IPA), data were collected through observations and interviews with key stakeholders. The findings highlight the importance of comprehensive promotion and marketing strategies, including online tourism marketing and community-based initiatives, to enhance tourist visits and boost the local economy. The research underscores the need for collaboration among all stakeholders to realize Bira Village’s full tourism potential sustainably.